Toxicity reduction and MMP-2 stimulation of papain and bromelain loaded in elastic niosomes - Manosroi A. (2014)
The elastic niosomes (Tween 61/cholesterol/sodium cholate at 1:1:0.1 molar ratio) loaded with the protease enzymes (papain and bromelain) gave the vesicular sizes of 109.5 to 143.9 nm with the negative zeta potential of -14.7 to -30.1 mv. The elastic niosomes loaded with the standard papain (PS), extracted papain (PE), standard bromelain (BS) and extracted bromelain (BE) showed deformability index (DI values) of 1.35, 1.81, 1.22 and 1.61 times higher than their corresponding non-elastic niosomes, respectively. The elastic niosomes did not only improve the entrapment efficiency of the enzymes over the non-elastic niosomes of about 1.35 times, but also reduced the toxicity on skin human fibroblasts by SRB assay of the PS, PE, BS and BE at 1.68, 2.10, 1.56 and 1.52 times, respectively. The relative MMP-2 stimulation of PS, PE, BS and BE loaded in elastic niosomes were 1.26±0.14, 1.34±0.15, 1.09±0.09 and 1.20±0.04 for the pro MMP-2 and 1.26±0.12, 1.41±0.23, 1.01±0.08 and 1.03±0.12 for the active MMP-2, respectively in comparing to the control which were similar activity to their free enzymes. The PE loaded in elastic niosomes gave superior characteristics (low cytotoxicity and high MMP-2 stimulation) to other enzymes. The elastic niosomes can enhance the chemical stability of PE, which exhibited higher remaining contents than the free PE of 1.36 times when kept at 27±2°C after 8 weeks. Therefore, the extracted papain loaded in elastic niosomes appeared to have potential to be developed as a topical product for scar treatment. Copyright © 2012 American Scientific Publishers All rights reserved.